The variation in crown-root morphology of anterior teeth assessed with cone-beam computed tomography - Xiao-ming WANG; Ling-zhi MA; Mei-fang YAN; Jun ZHENG; Mi WANG; Xue HUI (Dental Press Journal of Orthodontics, 2022)
ABSTRACT Objective: To determine the discrepancy of crown-root morphology of anterior teeth, using cone-beam computed tomography (CBCT), and to provide a guidance for proper torque expression. Methods: A total of eligible 200 CBCT were imported into Invivo v. 5.4 software, to obtain the middle labio-lingual sections of anterior teeth. AutoCAD 2007 software was applied to measure the crown-root angulation (Collum angle) and the angle formed by a tangent to the center of the labial surface and the long axis of the crown (labial surface angle). SPSS 18.0 was used for statistical comparisons of the two measurements, at the level of p< 0.05, and the Pearson correlation analysis was applied to investigate the association between the two measurements. Results: The value of Collum angle in maxillary central incisor was close to 0°. Significantly negative Collum angle in lateral incisors and maxillary canine, and positive value in mandibular canine were detected (p < 0.001). The labial surface angle in canine was significantly greater than the intra-arch incisors (p< 0.001), and no significant difference was detected between the central and lateral incisors (p > 0.05). Notably, there was also a significant positive correlation between the two measurements. Conclusions: The crown-root angulations were greatly different among anterior teeth. Accompanying the obvious crown-root angulations, the canines both in maxillary and mandibular arches presented considerable labial surface curvatures. Hence, equivalent deviation during bracket bonding might cause greater torque expression error and increase the risk of alveolar fenestration and dehiscence.